L’analyse des configurations du comportement industriel comme technique de prévision - Simmonds, W. (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
One important tool for forecasting in the field of applied economics has been largely overlooked—the identification and analysis of patterns of industrial behavior. The following paper shows how the method of detecting behavior patterns, and the factors which control them, can be utilized for analyzing the past economic performance of an industry and for predicting its likely performance in the future.This analysis has also revealed that when controlled by the same factors, different industries follow the same behavior pattern. This being so, it becomes possible to group industries together and reclassify them on the basis of their common major business characteristics. Of these, one of the most important is their mode of competition. This reclassification also enables us to know when we can transfer experience between industries (within the same group) and when we cannot do this (between industries in different groups).At the present time, significant changes are occurring in the economic, organizational and technical climates. New economic goals appear necessary for Canada and these are suggested. These changes are altering the importance of the factors controlling industrial behavior. The nature of these changes is considered and applied to the case of the chemical industry in the next decade. The analysis suggests what new factors will control this industry, and the direction and nature of the likely changes in it. Given this, an estimate of the economic changes can be made.Analysis of behavior patterns is, therefore, a powerful and essential tool for estimating the future behavior of industries, and of groups of industries, in the economy.